PENDEKATAN SEMANTIK TOSHIHIKO IZUTSU: KONSEPSI AGAMA (DIN) SEBAGAI KEPATUHAN - Arya Chandra Argadinata; Hudaeva, Andi Rosa (ADISAM PUBLISHER, 2024)
This study analyzes Toshihiko Izutsu's semantic approach in understanding the concept of